Hepatitis C virus acquisition among Egyptians: analysis of a 10‐year surveillance of acute hepatitis C. Issue 1 (22nd October 2014) - Mohsen, Amira; Bernier, Adeline; LeFouler, Lenaig; Delarocque‐Astagneau, Elisabeth; El‐Daly, Mai; El‐Kafrawy, Sherif; El‐Mango, Salwa; Abdel‐Hamid, Mohamed; Gadallah, Mohsen; Esmat, Gamal; Mohamed, Mostafa K.; Fontanet, Arnaud
Abstract Objective To identify current risk factors for hepatitis C virus (HCV) acquisition among Egyptians. Methods Patients with acute HCV were identified through a surveillance system of acute hepatitis in four fever hospitals in Egypt between 2002 and 2012. Case–control analysis was conducted, cases being incident acute symptomatic HCV and controls being acute hepatitis A identified at the same hospitals. The questionnaire covered iatrogenic, community and household exposures to HCV in the 1–6 months prior to onset of symptoms. Multivariate models were built to identify risk factors associated with HCV acquisition among non‐drug users and drug users separately. Results Among non‐drug users, hospital admission was independently associated with acute HCV infection (OR = 4.2, 95% CI = 1.7–10.5). Several iatrogenic procedures, for example admission in a surgery unit, sutures, IV injections and IV infusions, highly correlated with hospital admission, were also associated with acute HCV infection and could have been used in the final model instead of hospital admission. Among drug users, identified risk factors were multiple sexual relations (OR = 4.0, 95% CI = 1.1–14.7), intravenous drug use (OR = 3.9, 95% CI = 1.2–13.0) and shaving at the barbershops (OR = 8.7, 95% CI = 2.4–31.4). Illiteracy and marriage were significant risk factors in both groups. Conclusion Invasive medical procedures are still a major risk for acquiring new HCV infections in Egypt, as is illicit drug use in spreading HCV infection.